2020
DOI: 10.1007/s12630-020-01789-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding burnout and moral distress to build resilience: a qualitative study of an interprofessional intensive care unit team

Abstract: Objective The purpose of this study was to explore personal and organizational factors that contribute to burnout and moral distress in a Canadian academic intensive care unit (ICU) healthcare team. Both of these issues have a significant impact on healthcare providers, their families, and the quality of patient care. These themes will be used to design interventions to build team resilience. Methods This is a qualitative study using focus groups to elicit a better understanding of stakeholder perspectives on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 43 publications
(53 reference statements)
0
47
0
2
Order By: Relevance
“…Resilience might protect ICU workers from burnout, as reported in a Canadian qualitative study [ 18 ]. Resilience is described as the ability to face problems and adapt to adverse conditions [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 98%
“…Resilience might protect ICU workers from burnout, as reported in a Canadian qualitative study [ 18 ]. Resilience is described as the ability to face problems and adapt to adverse conditions [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 98%
“…Moral distress among healthcare professionals has been studied in various healthcare contexts including oncology [ 10 ], palliative care [ 3 ], psychiatry [ 11 ], pediatric care [ 12 ], surgical and medical care [ 13 ], emergency [ 14 ] and intensive care [ 15 – 17 ]. In a study Hancock et al [ 16 ] revealed three principal issues underlying the development of moral distress; namely, organizational issues, exposure to highly intense situations and poor team experiences. Several studies found that organizational constraints reduced the standard of patient care [ 18 ] and low staffing levels were found to be important sources of moral distress [ 11 , 16 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study Hancock et al [ 16 ] revealed three principal issues underlying the development of moral distress; namely, organizational issues, exposure to highly intense situations and poor team experiences. Several studies found that organizational constraints reduced the standard of patient care [ 18 ] and low staffing levels were found to be important sources of moral distress [ 11 , 16 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wellness is both a personal- and systems-level issue ( 11 ). Maintaining individual physical and mental health is usually taught at an early age or developed as part of a personal health strategy.…”
mentioning
confidence: 99%